Kecemasan Akademik Dan Self Regulated Learning Pada Mahasiswa Yang Sedang Mengerjakan Skripsi - Rahma, Ninda Aulia; Kristinawati, Wahyuni (Universitas Pahlawan Tuanku Tambusai, 2024)
Students as academics are expected to have their own awareness in developing their own potential and regulate their academic self to become intellectuals, scientists, practitioners and/or professionals, one of which is by making a final assignment or thesis. The demands and various obstacles in completing a thesis often encourage the emergence of academic anxiety, thus affecting students' self-regulated learning abilities in the process of completing the thesis. This research aims to empirically determine the relationship between academic anxiety and self-regulated learning of students who are working on their thesis. The research method used is quantitative with a correlational design. The sampling method used purposive sampling with respondents as many as 140 students who were working on their thesis. The research measurements used an academic anxiety measuring instrument (α = 0.859) and a self-regulated learning measuring instrument (α = 0.895). The research results prove that academic anxiety and self-regulated learning in students who are working on their thesis have a significant negative relationship (r = -0.463) with an effective contribution of academic anxiety of 21% to self-regulated learning. Keyword: Academic Anxiety; Self Regulated Learning; Student; Thesis